2009
DOI: 10.1186/1755-7682-2-11
|View full text |Cite
|
Sign up to set email alerts
|

The value of minilaparotomy for total hysterectomy for benign uterine disease: A comparative study with conventional Pfannenstiel and laparoscopic approaches

Abstract: Background: The aim of this paper is to review and compare the results obtained using the Pfannenstiel, laparoscopy and minilaparotomy approaches for total hysterectomy procedure in relation to benign uterine diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Th e incision length of Ͻ 7 cm was used in this study. A few studies have reported MH technique with a smaller transverse incision of Ͻ 6 cm (Hoff man and Lynch 1998; Sharma et al 2004;Alcalde et al 2007;Royo et al 2009). Special instruments, such as a uterine manipulator and a unique self-retaining elastic abdominal retractor were essential.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Th e incision length of Ͻ 7 cm was used in this study. A few studies have reported MH technique with a smaller transverse incision of Ͻ 6 cm (Hoff man and Lynch 1998; Sharma et al 2004;Alcalde et al 2007;Royo et al 2009). Special instruments, such as a uterine manipulator and a unique self-retaining elastic abdominal retractor were essential.…”
Section: Discussionmentioning
confidence: 97%
“…It might be an alternative technique for patients who may have a relative contraindication to LH. Th e other advantages of minilaparotomy approach were absence of CO 2 pneumoperitoneum, good cosmetic result, short learning curve and low expense (Alcalde et al 2007;Royo et al 2009). Th e cost of the Alexis ® retractor is approximately equal to only one disposable trocar at our institute.…”
Section: Discussionmentioning
confidence: 99%
“…It is a minimally invasive, feasible option, particularly in countries where laparoscopic hysterectomies are not available. In many reports, minilaparotomy hysterectomy has been compared to laparotomy and laparoscopic-assisted vaginal hysterectomy [12,13].…”
Section: Minilaparotomy Hysterectomymentioning
confidence: 99%
“…In many reports minilaparotomy hysterectomy has been compared to laparotomy and laparoscopic assisted vaginal hysterectomy. 15,16…”
Section: Which Techniques To Resect the Uterus In Malignant And Benigmentioning
confidence: 99%